PENGARUH MODEL PROBLEM BASED LEARNING DIBANTU FISHBONE DIAGRAM TERHADAP KETERAMPILAN PROSES SAINS BIOLOGI PESERTA DIDIK DI SMA NEGERI 1 KARANGNUNGGAL - Vita Meylani; Purwati Kuswarini; Nurhidayah Nurhidayah (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2018)
This research aims to know the influence of model learning Problem Based Learning (PBL) assisted Fishbone Diagram against the science process skills of learners in grades X SMA Negeri 1 Karangnunggal. This research was carried out in December 2016 until June 2017 in SMA Negeri 1 Karangnunggal. The research method used is the true experimental. The population in this research is the entire class X IPA SMA Negeri 1 Karangnunggal as much 7 classes consisting of 265 students and samples used 2 class taken using cluster random sampling techniques, namely class experiments and class controls. Data collection techniques in the form of the science process skills tests done before and after the activities of the learning process takes place. The instruments used are the science process skills test be reserved as many as 10 description of problem. Techniques of data processing and data analysis using t-test with level significant (α) = 0.05. Based on the results of the study indicate that there is influence of model learning Problem Based Learning (PBL) assisted Fishbone Diagram against the science process skills of learners in grades X SMA Negeri 1 Karangnunggal. Keywords: problem based learning, fishbone diagram, process skills.